home | career | drupal | java | mac | mysql | perl | scala | uml | unix  

Scala example source code file (Name.scala)

This example Scala source code file (Name.scala) is included in the alvinalexander.com "Java Source Code Warehouse" project. The intent of this project is to help you "Learn Scala by Example" TM.

Learn more about this Scala project at its project page.

Java - Scala tags/keywords

align, bindrec, comonad, cozip, distributive, equal, name, need, unzip, value

The Name.scala Scala example source code

package scalaz

import scala.annotation.tailrec

/** Call by name */
sealed abstract class Name[+A] {
  def value: A
}

/** Call by need */
final class Need[+A] private(private[this] var eval: () => A) extends Name[A] {
  lazy val value: A = {
    val value0 = eval()
    eval = null
    value0
  }
}

/** Call by value */
final case class Value[+A](value: A) extends Name[A]

object Name {
  def apply[A](a: => A) = new Name[A] {
    def value = a
  }
  def unapply[A](v: Name[A]): Option[A] = Some(v.value)

  implicit val name: Monad[Name] with BindRec[Name] with Comonad[Name] with Distributive[Name] with Traverse1[Name] with Zip[Name] with Unzip[Name] with Align[Name] with Cozip[Name] =
    new Monad[Name] with BindRec[Name] with Comonad[Name] with Distributive[Name] with Traverse1[Name] with Zip[Name] with Unzip[Name] with Align[Name] with Cozip[Name] {
      override def foldMap1[A, B: Semigroup](fa: Name[A])(f: A => B) = f(fa.value)
      override def foldLeft[A, B](fa: Name[A], z: B)(f: (B, A) => B) = f(z, fa.value)
      override def foldRight[A, B](fa: Name[A], z: => B)(f: (A, => B) => B) = f(fa.value, z)
      def alignWith[A, B, C](f: A \&/ B => C) = (a, b) => Name(f(\&/.Both(a.value, b.value)))
      def cozip[A, B](x: Name[A \/ B]) = x.value.bimap(Name(_), Name(_))
      def foldMapRight1[A, B](fa: Name[A])(z: A => B)(f: (A, => B) => B) = z(fa.value)
      def traverse1Impl[G[_], A, B](fa: Name[A])(f: A => G[B])(implicit G: Apply[G]) = G.map(f(fa.value))(Name(_))
      def unzip[A, B](a: Name[(A, B)]) = (Name(a.value._1), Name(a.value._2))
      def zip[A, B](a: => Name[A], b: => Name[B]) = Name((a.value, b.value))
      def point[A](a: => A) = Name(a)
      override def map[A, B](fa: Name[A])(f: A => B) = Name(f(fa.value))
      override def ap[A, B](fa: => Name[A])(f: => Name[A => B]) =
        Name(f.value apply fa.value)
      def bind[A,B](v: Name[A])(f: A => Name[B]): Name[B] = Name(f(v.value).value)
      def cobind[A, B](fa: Name[A])(f: Name[A] => B): Name[B] = Name(f(fa))
      override def cojoin[A](a: Name[A]): Name[Name[A]] = Name(a)
      def copoint[A](p: Name[A]): A = p.value
      def distributeImpl[G[_], A, B](fa: G[A])(f: A => Name[B])(implicit G: Functor[G]) =
        Name(G.map(fa)(a => f(a).value))
      @tailrec
      def tailrecM[A, B](f: A => Name[A \/ B])(a: A): Name[B] =
        f(a).value match {
          case -\/(a0) => tailrecM(f)(a0)
          case \/-(b) => Name(b)
        }
    }
  implicit def nameEqual[A: Equal]: Equal[Name[A]] = new Equal[Name[A]] {
    def equal(a1: Name[A], a2: Name[A]): Boolean = Equal[A].equal(a1.value, a2.value)
  }
}

object Need {
  def apply[A](a: => A): Need[A] = new Need(() => a)

  def unapply[A](x: Need[A]): Option[A] = Some(x.value)

  implicit val need: Monad[Need] with BindRec[Need] with Comonad[Need] with Distributive[Need] with Traverse1[Need] with Zip[Need] with Unzip[Need] with Align[Need] with Cozip[Need] =
    new Monad[Need] with BindRec[Need] with Comonad[Need] with Distributive[Need] with Traverse1[Need] with Zip[Need] with Unzip[Need] with Align[Need] with Cozip[Need] {
      override def foldMap1[A, B: Semigroup](fa: Need[A])(f: A => B) = f(fa.value)
      override def foldLeft[A, B](fa: Need[A], z: B)(f: (B, A) => B) = f(z, fa.value)
      override def foldRight[A, B](fa: Need[A], z: => B)(f: (A, => B) => B) = f(fa.value, z)
      def alignWith[A, B, C](f: A \&/ B => C) = (a, b) => Need(f(\&/.Both(a.value, b.value)))
      def cozip[A, B](x: Need[A \/ B]) = x.value.bimap(Need(_), Need(_))
      def foldMapRight1[A, B](fa: Need[A])(z: A => B)(f: (A, => B) => B) = z(fa.value)
      def traverse1Impl[G[_], A, B](fa: Need[A])(f: A => G[B])(implicit G: Apply[G]) = G.map(f(fa.value))(Need(_))
      def unzip[A, B](a: Need[(A, B)]) = (Need(a.value._1), Need(a.value._2))
      def zip[A, B](a: => Need[A], b: => Need[B]) = Need((a.value, b.value))
      def point[A](a: => A) = Need(a)
      override def map[A, B](fa: Need[A])(f: A => B) = Need(f(fa.value))
      override def ap[A, B](fa: => Need[A])(f: => Need[A => B]) =
        Need(f.value apply fa.value)
      def bind[A, B](v: Need[A])(f: A => Need[B]): Need[B] = Need(f(v.value).value)
      def cobind[A, B](fa: Need[A])(f: Need[A] => B): Need[B] = Need(f(fa))
      override def cojoin[A](a: Need[A]): Need[Need[A]] = Need(a)
      def copoint[A](p: Need[A]): A = p.value
      def distributeImpl[G[_], A, B](fa: G[A])(f: A => Need[B])(implicit G: Functor[G]) =
        Need(G.map(fa)(a => f(a).value))
      @tailrec
      def tailrecM[A, B](f: A => Need[A \/ B])(a: A): Need[B] =
        f(a).value match {
          case -\/(a0) => tailrecM(f)(a0)
          case \/-(b) => Need(b)
        }
    }
  implicit def needEqual[A: Equal]: Equal[Need[A]] = new Equal[Need[A]] {
    def equal(a1: Need[A], a2: Need[A]): Boolean = Equal[A].equal(a1.value, a2.value)
  }
}

object Value {
  implicit val value: Monad[Value] with BindRec[Value] with Comonad[Value] with Distributive[Value] with Traverse1[Value] with Zip[Value] with Unzip[Value] with Align[Value] with Cozip[Value] =
    new Monad[Value] with BindRec[Value] with Comonad[Value] with Distributive[Value] with Traverse1[Value] with Zip[Value] with Unzip[Value] with Align[Value] with Cozip[Value] {
      override def foldMap1[A, B: Semigroup](fa: Value[A])(f: A => B) = f(fa.value)
      override def foldLeft[A, B](fa: Value[A], z: B)(f: (B, A) => B) = f(z, fa.value)
      override def foldRight[A, B](fa: Value[A], z: => B)(f: (A, => B) => B) = f(fa.value, z)
      def alignWith[A, B, C](f: A \&/ B => C) = (a, b) => Value(f(\&/.Both(a.value, b.value)))
      def cozip[A, B](x: Value[A \/ B]) = x.value.bimap(Value(_), Value(_))
      def foldMapRight1[A, B](fa: Value[A])(z: A => B)(f: (A, => B) => B) = z(fa.value)
      def traverse1Impl[G[_], A, B](fa: Value[A])(f: A => G[B])(implicit G: Apply[G]) = G.map(f(fa.value))(Value(_))
      def unzip[A, B](a: Value[(A, B)]) = (Value(a.value._1), Value(a.value._2))
      def zip[A, B](a: => Value[A], b: => Value[B]) = Value((a.value, b.value))
      def point[A](a: => A) = Value(a)
      def bind[A, B](v: Value[A])(f: A => Value[B]): Value[B] = f(v.value)
      def cobind[A, B](fa: Value[A])(f: Value[A] => B): Value[B] = Value(f(fa))
      override def cojoin[A](a: Value[A]): Value[Value[A]] = Value(a)
      def copoint[A](p: Value[A]): A = p.value
      def distributeImpl[G[_], A, B](fa: G[A])(f: A => Value[B])(implicit G: Functor[G]) =
        Value(G.map(fa)(a => f(a).value))
      @tailrec
      def tailrecM[A, B](f: A => Value[A \/ B])(a: A): Value[B] =
        f(a).value match {
          case -\/(a0) => tailrecM(f)(a0)
          case \/-(b) => Value(b)
        }
    }
  implicit def valueEqual[A: Equal]: Equal[Value[A]] = new Equal[Value[A]] {
    def equal(a1: Value[A], a2: Value[A]): Boolean = Equal[A].equal(a1.value, a2.value)
  }
}

Other Scala examples (source code examples)

Here is a short list of links related to this Scala Name.scala source code file:



my book on functional programming

 

new blog posts

 

Copyright 1998-2019 Alvin Alexander, alvinalexander.com
All Rights Reserved.

A percentage of advertising revenue from
pages under the /java/jwarehouse URI on this website is
paid back to open source projects.